Pengaruh Quick Ratio, Total Asset Turnover, Dan Debt To Asset Ratio Terhadap Return On Asset Pada PT Adhi Karya Tbk Periode 2014-2024 - Mayulis Styawati; Lina Nofiana (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to determine and analyze the extent of the influence of Quick Ratio, Total Asset Turnover, and Debt to Asset Ratio on Return On Asset at PT Adhi Karya Tbk for the 2014 2024 period, both partially and simultaneously. The research method used is quantitative, research method based on post-positivist philosophy, used to research a specific population or sample, data collection using research instruments, quantitative/statistical data analysis, with the aim of describing and testing established hypotheses. The results show that Quick Ratio has significant partial effect (t-count 2.894 > t-table 2.364 with a significance value of 0.023 < 0.05). The test results for Total Asset Turnover indicate a significant positive effect (t-count 2.773 > t-table 2.634 with a significance value of 0.028 < 0.05). The test results for Debt to Asset Ratio show has no significant effect (t-count 0.375 < 1-table 2.634 with a significance value of 0.719 > 0.05). Simultaneously, Quick Ratio, Total Asset Turnover, dan Debt to Asset Ratio have a significant effect on Return On Asset (f-count 18.084 > f-table 4.35 with a significance value of 0.001 < 0.05)